2016
DOI: 10.1093/mnras/stw2315
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fitting of Gaussian-apodized or under-resolved emission lines in Fourier transform spectra providing new insights on the velocity structure of NGC 6720

Abstract: An analysis of the kinematics of NGC 6720 is performed on the commissioning data obtained with SITELLE, the Canada-France-Hawaii Telescope's new imaging Fourier transform spectrometer. In order to measure carefully the small broadening effect of a shell expansion on an unresolved emission line, we have determined a computationally robust implementation of the convolution of a Gaussian with a sinc instrumental line shape which avoids arithmetic overflows. This model can be used to measure line broadening of typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 29 publications
(27 reference statements)
1
58
0
Order By: Relevance
“…The data were reduced using ORBS, SITELLE's dedicated data reduction software (Martin, Drissen & Joncas 2015;Martin, Prunet & Drissen 2016). Fig.…”
Section: O B S E Rvat I O N S a N D Data R E D U C T I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were reduced using ORBS, SITELLE's dedicated data reduction software (Martin, Drissen & Joncas 2015;Martin, Prunet & Drissen 2016). Fig.…”
Section: O B S E Rvat I O N S a N D Data R E D U C T I O Nmentioning
confidence: 99%
“…A fitting routine using the correct instrument line shape (essentially a convolution of a sinc function with a Gaussian) described in Martin et al (2016) was then applied to each spectrum, providing radial velocities and reliable uncertainties (Table 1, where blobs are listed in increasing order of radial velocity, from the most blueshifted to the most redshifted). In 51 cases, the fainter [N II] 6548 line was clearly detected and fitted.…”
Section: Blob Identification and Radial Velocitiesmentioning
confidence: 99%
“…As they come out of the reduction pipeline, datacubes have a pixel-to-pixel velocity error estimated to be of the order of 0.1 km s −1 at R = 5000. Additional correction is applied to the absolute wavelength calibration using the skylines centroid map as described in Martin et al (2018) resulting in an accuracy of ∼1 km s −1 on the measured relative velocities across the FOV (see appendix B of Martin et al 2016 for details).…”
Section: Data Reduction and Calibrationsmentioning
confidence: 99%
“…The FWHM of the sinc function is known and fixed since it depends only on the sampling and the maximum optical path displacement of the interferogram scan (Martin et al 2016;Drissen et al 2019). As shown in the work of Martin et al (2016), when natural line broadening is observed, a sinc convolved with a Gaussian function can be used to properly recover the line parameters. If so, the line model has three varying parameters (amplitude, velocity, and broadening of the Gaussian).…”
Section: Data Reduction and Calibrationsmentioning
confidence: 99%
“…The data reduction was performed with ORBS (v. 4.0-DR1beta; Martin et al 2015Martin et al , 2016. ORBS is an automatic data reduction software designed for iFTS data obtained with SITELLE freely available on the web 2 .…”
Section: Data Reduction and Lines Fittingmentioning
confidence: 99%